Hepatic Angiomyolipoma - Bakhotmah, Mohamad Abid (Hindawi Publishing Corporation, 1994)
Hepatic angiomyolipomas are rare benign tumours. First reported by Ishak in 1976. Since then, the world literature showed only 32 cases including 8 autopsy findings. In this paper a retrospective analysis of the published data will be presented and the first report ofthe preoperative colour doppler and intraoperative sonography appearances will also be described.